Ax³+bx+c разделили х-3, (то есть при х=3) и получили остаток 11. Разделим ax³+bx+c на х-3: ax³+bx+c Ι_x-3_ ax³-3ax² Ι ax²+3ax ------------ 3ax²+bx 3ax²-9ax ------------------ bx+9ax+c - это остаток, который равен 11. При х=3 остаток 9ax+bx+c=9*3a+3*b+c=27a+3*b+c=11. ⇒ Ответ: 27a+3b+c=11.
Answers & Comments
Verified answer
Ax³+bx+c разделили х-3, (то есть при х=3) и получили остаток 11.Разделим ax³+bx+c на х-3:
ax³+bx+c Ι_x-3_
ax³-3ax² Ι ax²+3ax
------------
3ax²+bx
3ax²-9ax
------------------
bx+9ax+c - это остаток, который равен 11.
При х=3 остаток 9ax+bx+c=9*3a+3*b+c=27a+3*b+c=11. ⇒
Ответ: 27a+3b+c=11.